2019
DOI: 10.1136/bmjopen-2019-033817
|View full text |Cite
|
Sign up to set email alerts
|

Does tonsillectomy reduce medical care visits for pharyngitis/tonsillitis in children and adults? Retrospective cohort study from Sweden

Abstract: ObjectiveTo assess the effectiveness of tonsillectomy/adenotonsillectomy in reducing medical care visits for pharyngitis or tonsillitis in children and adults with chronic/recurrent tonsillitis.DesignRetrospective cohort study.SettingData were retrieved from the VEGA register, a comprehensive regional cohort in Sweden.Participants1044 children (<15 years) and 2244 adults.InterventionTonsillectomy/adenotonsillectomy compared with no surgical treatment.Main outcome measuresChanges in yearly mean rates of medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The Paradise criteria are referred to for the indications for surgery in all three countries guidelines, but the Swedish guidelines are phrased so that only three infections can qualify for surgery 8. A study confirmed that few patients in Sweden seem to meet the Paradise criteria 22 23. However, the criteria cover only recurrent tonsillitis and not surgical indications for chronic tonsillitis.…”
Section: Discussionmentioning
confidence: 96%
“…The Paradise criteria are referred to for the indications for surgery in all three countries guidelines, but the Swedish guidelines are phrased so that only three infections can qualify for surgery 8. A study confirmed that few patients in Sweden seem to meet the Paradise criteria 22 23. However, the criteria cover only recurrent tonsillitis and not surgical indications for chronic tonsillitis.…”
Section: Discussionmentioning
confidence: 96%
“…Tonsilitis is an inflammation of the tonsils. It is a viral infection and sometimes it may bacterial also [1,2] . The common symptoms of tonsilitis is sore throat, fever, enlargement of the tonsils, trouble in swallowing and lymphadenopathy [3,4] .…”
mentioning
confidence: 99%